Serum Magnesium Levels in Hypothyroid And Euthyroid Patients at a Tertiary Care Center: A Comparative Cross-Sectional Study - Binit Kumar Sharma; Buddhi Raj Pokhrel; Swaichhya Gautam; Laxmi Poudel; Binaya Tamang; Jharana Shrestha; Narayan Gautam; Sneha Jaiswal (Journal of Universal College of Medical Sciences, 2025)
INTRODUCTION Magnesium (Mg) plays a role in thyroid hormone metabolism, immune regulation, and oxidative stress control. However, studies comparing Mg levels in hypothyroid and euthyroid individuals have yielded inconsistent results. Region-specific data from Western Nepal are limited. MATERIAL AND METHODS This cross-sectional analytical study included 150 primary hypothyroid and 150 euthyroid adults attending a tertiary care center in Southwestern Nepal between May 2023 and April 2024. Thyroid status was assessed using serum TSH, free T4 (fT4), and free T3 (fT3). Serum Mg levels were measured. Group comparisons and correlations were analyzed using non-parametric tests, with p < 0.05 considered statistically significant. RESULTS Mg levels were significantly higher in hypothyroid individuals compared to euthyroid controls (p = 0.001), with the difference significant only in the 21–40 year age group (p = 0.008). Median Mg levels in both groups were within the reference range. When classified into euthyroid, subclinical, and overt hypothyroid categories, both hypothyroid groups showed higher Mg levels than the euthyroid group. Mg exhibited weak but significant positive correlations with TSH, age, and BMI. CONCLUSION Hypothyroid individuals exhibited higher serum Mg levels than euthyroid controls, predominantly in the 21 – 40 year age group. Well-designed clinical trials are warranted to evaluate the therapeutic potential and clinical relevance of Mg in thyroid dysfunction.